Effect of scapular stabilization exercises on subacromial pain (impingement) syndrome: a systematic review and meta-analysis of randomized controlled trials - Zhong, Ziyi; Zang, Wanli; Tang, Ziyue; Pan, Qiaodan; Yang, Zhen; Chen, Bin (Frontiers in Neurology, 2024)
Objective To evaluate the effectiveness of scapular stabilization exercises (SSE) in the treatment of subacromial pain syndrome (SAPS). Methods Clinical randomized controlled trials (RCTs) on SSE in the treatment of SAPS were searched electronically in PubMed, Science Direct, Cochrane Central Register of Controlled Trials (CENTRAL), EBSCOhost, Physiotherapy Evidence Database (PEDro), Web of Science, and other databases from 2000 to 2022, supplemented by manual search. Final RCTs were selected based on inclusion and exclusion criteria, and the Physiotherapy Evidence Database scale was used to evaluate the methodological quality of the study. A meta-analysis was conducted on data using the RevMan5.4 software. Results Eight RCTs involving 387 participants were included. The meta-analysis showed that the experimental group (SSE) had greater improvements in the Visual Analog Scale score [Weighted Mean Difference (WMD) = −0.94, 95% CI (−1.23, −0.65), p < 0.001] and the Shoulder Pain and Disability Index score [WMD = −10.10, 95% CI (−18.87, −1.33), p = 0.02] than the control group (conventional physical therapy). However, range of motion (ROM) was not found to be greater in the experimental group than in the control group. Conclusion Existing evidence moderately supports the efficacy of SSE for reducing pain and improving function in SAPS, without significant improvement in ROM. Future research should focus on larger, high-quality, standardized protocols to better understand SSE’s effects across diverse SAPS populations, treatment, and outcome measures. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=307437, CRD42022307437.